Porphyromonas gingivalis : Its virulence and vaccine - Nymphea Pandit; Radha Changela; Deepika Bali; Priyanka Tikoo; Shalini Gugnani (Wolters Kluwer Medknow Publications, 2015)
Background: The microbial florae in adult periodontitis lesions are comprised of anaerobic rods with Porphyromonas gingivalis as one of the major components (Slots 1976; Slots 1979; and Tanner et al., 1979). P. gingivalis is a black-pigmented gram-negative anaerobic rod and a secondary colonizer of dental plaque requiring antecedent organisms. The presence of this organism either alone or as a mixed infection with other bacteria and with the absence of beneficial species appears to be essential for disease activity. It is a predominant member of the subgingival microbiota in disease. It possesses and "excretes" numerous potentially toxic virulence factors. Aim of this study is to perform a systematic review of studies on P. gingivalis and its virulence factors with a special focus on its vaccine. Materials and Methods: An electronic and manual search based on agreed search phrases between the primary investigator and a secondary investigator was performed for the literature review till January 2014. The articles that were identified by this systematic review (total of 190) were analyzed in detail, which included the study of inference and conclusion. Conclusions: Within the limits of this systematic review, it can be concluded that P. gingivalis induce immune inflammatory response in periodontitis subjects. Therapeutic vaccines need to be developed and studied for their efficacy in controlling periodontitis.